FEATURES OF THE INFLUENCE OF THE MODERN ENVIRONMENT ON THE INNOVATIVE DEVELOPMENT OF INTEGRATED STRUCTURES OF ENTERPRISE INTERACTION IN WARTIME CONDITIONS - Baula, Oleksii V. (Journal of Strategic Economic Research, 2025)
The article considers and defines the features of innovative development of integrated structures. The innovative activity of enterprise interaction in a single economic space is substantiated. Factors of influence on the innovative development of integrated structures of enterprise interaction in martial law conditions are formed, taking into account foreign experience. Based on the theory of innovation clusters and the concept of growth cycles, conclusions are formed that in a market environment, the innovative development of integrated structures of enterprise interaction in martial law conditions is associated with the distribution and cooperation, provision of resources and, accordingly, the implementation of procedures for the effective implementation of the life innovation cycle. Factors that have an impact, form a favorable environment, allow integrated structures in interaction to be capable of innovations, demand formation; development of supporting sectors of the economy; to be stable in the market and to strategize in conditions of post-war recovery. Enterprises in interaction constitute the basic competitive basis of the country in war conditions, forming the necessary space for the development of the military and post-war economy.